Advancements in CFD Simulation and Dynamic Modeling for Enhanced Performance of Multi-Compartment Rotor Compressed Combustion Engines - Nnadikwe Johnson; Samuel Hanotu Kwelle (SEAN Institute, 2025)
This research explores the potential of dynamic mathematical model simulation for multi-compartment rotor compressed combustion engines to revolutionize power generation by enhancing fuel burning efficiency. By leveraging advanced computational fluid dynamics (CFD) techniques, this study investigates the impact of modifying the engine design to induce turbulence through squish and tumble flows on fuel-air mixing and combustion efficiency. The proposed design features multiple compartments on the rotor crown, comprising three small chambers spaced 120º apart. CFD simulations using FLUENT software demonstrate significant improvements in tumble ratio (35% increase) and squish velocity (31% increase) compared to the base engine. These findings suggest that the modified engine design can enhance fuel-air mixing and combustion performance, leading to improved overall engine efficiency. This research contributes to the development of more efficient and environmentally-friendly power generation technologies, paving the way for groundbreaking advancements in combustion engine design.